Disease recurrence after right hemicolectomy in Scotland: Is there rationale to adopt complete mesocolic excision (CME)?. Issue 5 (October 2022) - H M Metcalfe, Kiloran; Knight, Katrina; McIntosh, Stuart; Hunter, Ross; MacKay, Craig; McCabe, Gerard; Sahni, Dhruv; Ramsay, George; Roxburgh, Campbell; Richards, Colin
Abstract: Aims: Complete mesocolic excision (CME) has been proposed as a way to improve the oncological outcomes in patients with colon cancer. To investigate whether there is rationale for adopting the technique in Scotland, our aim was to define the incidence of disease recurrence following standard right hemicolectomy and to compare this with published CME outcomes. Methods: Data was collected on consecutive patients undergoing right or extended right hemicolectomy for colonic adenocarcinoma (2012–2017) at three hospitals in Scotland (Raigmore Hospital, Aberdeen Royal Infirmary and Glasgow Royal Infirmary). Emergency or palliative surgery was excluded. Patients were followed up with CT scans and colonoscopy for a minimum of 3 years. Results: 689 patients (M 340, F 349) were included. 30-day mortality was 1.6%. Final pathological stage was Stage I (14%), Stage II (49.8%) and Stage III (36.1%). During follow-up, 10.5% developed loco-regional recurrence and 12.2% developed distant metastases. The 1, 3 and 5-year disease-free survival (DFS) was 94%, 84% and 82% respectively. Primary determinants of recurrence were T stage (p < 0.001), N stage (p < 0.001), apical node involvement (p < 0.001) and EMVI (p < 0.001). When compared to the literature, 30-day mortality was lower than many published series and DFS rates were similar to the largest CME study to date (4 year DFS 85.8% versus 83%). Conclusion: The outcomes of patients undergoing right hemicolectomy in Scotland compare favourably with many published CME studies. The technique demands further evaluation before it can be recommended for adoption into routine surgical practice. Highlights: 1. Most evidence for complete mesocolic excision (CME) is from historical controls. 2. We provide up to date evidence of outcomes achieved in colon cancer without CME. 3. We question a universal adoption of CME and propose further evidence is needed.